2009
DOI: 10.1155/2009/456208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxysterol‐Induced Apoptosis of Vascular Smooth Muscle Cells on Experimental Hypercholesterolemia

Abstract: Smooth muscle cells (SMCs) undergo changes related to proliferation and apoptosis in the physiological remodeling of vessels and in diseases such as atherosclerosis and restenosis. Recent studies also have demonstrated the vascular cell proliferation and programmed cell death contribute to changes in vascular architecture in normal development and in disease. The present study was designed to investigate the apoptotic pathways induced by 25-hydroxycholesterol in SMCs cultures, using an in vivo/in vitro cell mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…A marked increase in Bax protein levels was also observed, possibly mediated by p53 [35]. These results indicate that, under our experimental conditions, 25-HC-induced apoptosis is mediated by p53.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A marked increase in Bax protein levels was also observed, possibly mediated by p53 [35]. These results indicate that, under our experimental conditions, 25-HC-induced apoptosis is mediated by p53.…”
Section: Discussionsupporting
confidence: 65%
“…We previously characterized 25OHC-induced SMC apoptosis by studying antiapoptotic and proapoptotic (bcl-2, bcl-xl and bax) gene expression [35]. The objective of the present study was to characterize 25-HC-induced SMC apoptosis by studying of caspase-3, c-myc, and p53 gene expression in SMC-C, SMC-Ch, and SMC-Ch-FO cultures.…”
Section: Introductionmentioning
confidence: 96%
“…Hypercholesterolemia has also been shown to modulate apoptosis in other tissue types. For example, Perales et al showed upregulated BAX expression in vascular smooth muscle cells exposed to 25-hydroxycholesterol [41]. Therefore, the majority of these results demonstrates that there is a strong relationship between increased cardiac apoptosis and hypercholesterolemia, although different models of hypercholesterolemia display varying constellations of altered apoptotic markers.…”
Section: Discussionmentioning
confidence: 99%
“…The data led us to suppose that the major contributor to apoptosis in ischaemic‐reperfused myocardium is the oxidative stress originating from blood or non‐myocytes. Thus, we examined cells incubated with 25‐OH‐cholesterol, which can be involved in atherosclerosis, one of the main causes of myocardial infarction (Perales et al, 2009). It was chosen as an example of oxygenated derivative of cholesterol that may be formed in vivo during reperfusion as a direct result of the increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%